Political Marketing on Social Media (Instagram Analysis Study of Serang Mayoral Candidates in 2024) - Yonita, Lingga (Riwayat: Educational Journal of History and Humanities, 2025)
This research is motivated by the increased political activity through social media during the 2024 Serang mayoral election campaign. Through Instagram, the three pairs of Serang mayoral candidates distributed their political messages through various posts detailing their campaign activities. The purpose of this study was to determine how the Serang mayoral candidates engaged in political marketing to gain public support through their posts on Instagram. This study uses a qualitative method. Data analysis uses qualitative content analysis by observing the Instagram accounts @hjriamaryana, @budirustandi.official, and @syafrudinofficial during the campaign period of September 25 - October 25, 2024 through 4 categories of Niffenegger's Political Marketing including product, price, place, and promotion. This study found that political communication messages displayed on the Instagram account of the Serang Mayoral Candidate have a variety of themes and types of content uploaded.